Analisis Manajemen Layanan Teknologi Informasi Menggunakan Framework ITIL V4 pada PT Puskomedia Indonesia Kreatif (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study analyzes the implementation of the ITIL V4 Service Value System (SVS) in managing information technology services at PT Puskomedia Indonesia Kreatif. The research aims to evaluate the alignment of the company’s service management Practices with ITIL V4 best Practices, focusing on issues related to digital documentation and incident tracking. A qualitative case study approach was used, with data collected through observation, interviews, and documentation review. The results show that the company has applied several ITIL V4 components, particularly in service delivery and support, collaboration, and responsiveness to customer needs. However, Governance and documentation processes remain mostly manual, and incident tracking lacks digital monitoring, limiting data-driven evaluation. Core Practices such as Incident Management, Service Request Management, and Change Enablement are implemented but have not reached optimal maturity due to the absence of automation, SLA documentation, and structured change records. The study highlights the need for an integrated service desk system, Governance dashboard, and Continual Improvement Register (CIR) to strengthen transparency, accountability, and long-term service quality.